SELEKSI PANITIA PEMILIHAN KECAMATAN (PPK) PADA PEMILIHAN KEPALA DAERAH (PILKADA) TAHUN 2020 DI KOTA MANADO (STUDI DI KOMISI PEMILIHAN UMUM KOTA MANADO) - Yerik ., Agama; Burhan ., Niode; Donald K. Monintja (AGRI-SOSIOEKONOMI, 2021)
This research aims to study and analyze scientifically the Selection of the District Election Committee in the 2020 Regional Head Election in Manado City, viewed from the regulatory aspect. The research method used in this study is a qualitative approach with a descriptive analysis method to comprehensively disclose the selection of the District Election Committee in the 2020 Regional Head Election in Manado City. Respondents in this study amounted to 13 people were determined by purposive sampling with a research focus using the theory of Mifta Thoha (2008), namely the patronage system, merit system and career system. Data was collected by means of interviews, observation and documentation.Â  Data analysis used a triangulation approach. The results show that of the three recruitment systems that have been analyzed by researchers related to the patronage system, the Merit System and the career system of these three systems, of course, each of them has an influence, weakness and strength. This becomes a recommendation for the selection process of the upcoming sub-district election committee so that in the selection process, the General Ellections Comission will be truly professional and accountable, not looking at one interest.